Evaluation of Implementing the Video in University for Online Learning Amid Covid-19 Pandemic - Lia Amalia (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the results of the evaluation of the implementation of video at universities related to online learning during the Covid-19 pandemic. This study uses a qualitative approach with the evaluation method of the Stufflebeam model, namely CIPP (Context, Input, Process, Product). Data were collected through documentation, observation, and interviews. The data were analyzed through the stages of data reduction, data presentation and concluding. The results of the study concluded that the use of videos at universities during online learning activities was good. The shortcomings found were in the input aspect to improve the digital competence of lecturers in mastering the latest technology as a learning medium. The learning process must be improved again to stimulate students to be more active during discussions. Meanwhile, the product aspect related to learning outcomes also shows a decrease in student achievement and attitudes in motivating themselves to learn. The results of this study have implications for the understanding of lecturers and universities about the readiness of facilities and technology for online learning activities.